Antimicrobial activity of selected fatty acids and their derivatives - ZHANG Xi; YANG Ming; SONG Fei; ZHANG Hui; FENG Fengqin (浙江大学学报. 农业与生命科学版, 2013)
Fatty acids are ubiquitous molecules, which are typically bounded to other compounds such as glycerol, sugar or phosphate head groups to form various derivatives. They have diverse and potent biological activities, such as anti-inflammatory, anti-tumor, anti-protozoan, antiviral, antifungal and antibacterial activities. Although the antimicrobial activity of fatty acids and their derivatives has been well known for many years, the structural and functional features causing them to prevent microbial growth or survival are still unknown.The purpose of the present study was to find out the correlation between structural features and the antimicrobial activities. At first step, it was necessary to evaluate the efficacy of various fatty acids and their derivatives to control the growth of Escherichia coli O157: H7 and Candida albicans.The microorganisms used for screening studies were common in food (E. coil O157: H7) and clinical specimens (C. albicans) and were individually maintained through monthly transfers to the respective fresh medium (E. coil O157: H7 in trypticase soy broth at 37 ℃; C. albicans in Sabouraud-Dextrose broth at 30 ℃) and were stored at 4 ℃. Stock cultures were inoculated and grown on respective broth for 18-24 h to prepare active and working cultures. The tested samples included 10 kinds of saturated fatty acids, six different unsaturated fatty acids, nine kinds of monoacylglycerols, two types of fatty acid methyl esters, three kinds of fatty acid ethyl esters and four classes of fatty alcohols. They were dissolved in 95% ethanol, sterile Tween-80 (final concentrations of ethanol and Tween-80 were 1.5%, respectively) and then were filter-sterilized using a 0.22 μm pore size membrane filter. Ethanol and Tween-80 controls were used for each experiment to ensure that any observed inhibition was not due to them. Antibiotics were dissolved in 1.5% ethanol and tween-80 used as positive controls. The respective broths which contained 0.015, 0.007 5 mol/L fatty acids and their derivatives were inoculated with approximately 1.0×105 -5.0×105 CFU/mL of active cultures, then they were incubated for 24 h at the optimum temperature. Samples (100 μL) were removed and immediately diluted 10-fold in sterile physiological saline. The number of viable microorganisms was determined through a standard plate count technique.All the tested medium-chain fatty acids (C8-12) and their corresponding chain monoacylglycerols, long-chain unsaturated fatty acids (> C12) showed more antimicrobial activities than fatty alcohols. Long-chain fatty acids, fatty acid methyl esters and fatty acid ethyl esters had feeblish antimicrobial activity. Of the saturated fatty acids, The C < 12 saturated fatty acids were more active than the C > 13 fatty acids; as compared with their saturated counterparts, the C14: 1, C16: 1, C16: 2 unsaturated fatty acids were more highly active, however, the linolenic acid (C18: 3) was not very active. The fatty acid etherified with the alcohol and methanol showed no inhibition. The 1, 3-dilaurin was less active than the fatty acid. The monoglyceride was proved to be more active.In sum, the chain length, substituent, numbers and position of double bond are the important factors influencing the antimicrobial activity of fatty acids and their derivatives.